Discovery of Novel TULP4/ACTN4/EWSR1/ACTB::MYB and ESRRG::DNM3 Fusions Expands Molecular Landscape of Adenoid Cystic Carcinoma beyond Fusions between MYB/MYBL1 and NFIB Genes - Skálová, Alena; Klubícková, Natálie; Bradová, Martina; Agaimy, Abbas; Rupp, Niels J.; Damjanov, Ivan; Kolnikova, Georgina; Martínek, Petr; Šteiner, Petr; Grossmann, Petr; Vanecek, Tomas; Michal, Michal; et al. (American Journal of Surgical Pathology, 2024)
Adenoid cystic carcinoma (AdCC) is one of the most common salivary gland malignancies and occurs in all major and minor salivary gland and seromucous gland sites. AdCCs of salivary gland origin have long been categorized as fusiondefined carcinomas owing to the almost consistent presence of fusion genes MYB::NFIB, or less commonly MYBL1::NFIB. We collected a cohort of 95 cases of AdCC, which were largely characterized by canonical fusions MYB::NFIB (49 cases) or MYBL1::NFIB (9 cases). In additional 11 cases of AdCC, rearrangements in MYB or NFIB genes were detected by FISH. In addition, NGS revealed novel noncanonical fusion transcripts EWSR1::MYB; ACTB::MYB; ESRRG::DNM3, MYB:: TULP4, and ACTN4::MYB, each of them in 1 case. The tumors that showed noncanonical fusions had features of metatypical AdCC with a diverse architecture, lobulated multinodular growth pattern, and hypercellular peripheral palisading of nuclei (2 cases), tubular hypereosinophilia (2 cases), and pale eosinophilic to vacuolated (bubbly) cytoplasm (3 cases). Our study documented 3 cases of AdCC of salivary glands harboring novel gene fusions TULP4::MYB, ACTN4::MYB, and ACTB::MYB, in 1 case each, which have not been described before. A rare EWSR1::MYB fusion was detected in 1 case. Moreover, 1 case of sinonasal metatypical AdCC showed EWSR1 rearrangement detected by FISH. Also, 1 case with an ESRRG::DNM3 fusion of unknown significance is described in this study. These discoveries illustrate how broad molecular profiling will expand understanding of changes in known entities.
CRIS-Team Scopus Importer:2024-09-20
Keywords: adenoid cystic carcinoma; novel ESRRG::DNM3 gene fusion; salivary gland neoplasm; sinonasal; TULP4/ACTN4/EWSR1/ACTB::MYB gene fusion